PENGARUH METODE PEMBELAJARAN DISKUSI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI KELAS VIII DI SMP AN-NUR BULULAWANG MALANG - Muhamad Ilyas; Chalimatus Sa’dijah; Fita Mustafida (VICRATINA, 2019)
This study aims to determine how the influence of discussion learning methods on student learning outcomes on PAI subjects SMP An-Nur Bululawang Malang.  The problem that often occurs is feeling bored and less active in following the learning process. Students become unenthusiastic and enthusiastic in learning, the atmosphere becomes stiff and monotonous. With the implementation of a discussion learning system, it is expected to change the way students learn from passive learning to be active, so that it has an impact on improving learning outcomes. This research is a type of quantitative research using questionnaires, observation and documentation. Data collection techniques used were questionnaires and observations to obtain data about the application of discussion learning (X) and documentation to obtain data about student learning achievement (Y). The research data collected was analyzed using the t-test hypothesis analysis technique.